Small Molecule Inhibitors of CRM1 - Bibiana I. Ferreira; Bibiana I. Ferreira; Bibiana I. Ferreira; Bastien Cautain; Bastien Cautain; Inês Grenho; Inês Grenho; Inês Grenho; Wolfgang Link (Frontiers in Pharmacology, 2020)
The transport through the nuclear pore complex is used by cancer cells to evade tumor-suppressive mechanisms. Several tumor-suppressors have been shown to be excluded from the cell nucleus in cancer cells by the nuclear export receptor CRM1 and abnormal expression of CRM1 is oncogenic. Inhibition of CRM1 has long been postulated as potential approach for the treatment of cancer and to overcome therapy resistance. Furthermore, the nuclear export of viral components mediated by the CRM1 is crucial in various stages of the viral lifecycle and assembly of many viruses from diverse families, including coronavirus. However, the first nuclear export inhibitors failed or never entered into clinical trials. More recently CRM1 reemerged as a cancer target and a successful proof of concept was achieved with the clinical approval of Selinexor. The chemical complexity of natural products is a promising perspective for the discovery of new nuclear export inhibitors with a favorable toxicity profile. Several screening campaigns have been performed and several natural product-based nuclear export inhibitors have been identified. With this review we give an overview over the role of CRM1-mediated nuclear export in cancer and the effort made to identify and develop nuclear export inhibitors in particular from natural sources.